Natural Disasters in the United States
VII, 270 p. 23 illus., 19 illus. in color.
Keywords: This volume examines the history of natural disasters in the United States and the nation's ongoing struggles with long-term disaster preparedness and response. It explores the political, economic, and cultural factors that have shaped the country's vulnerability. It highlights why, despite its vast resources, the United States has remained one of the most resistant actors in recognizing and mitigating disaster risk. Bringing together contributions from a variety of fields, this book analyzes the role of political institutions, media narratives, and cultural perceptions in shaping disaster policy. It examines key historical events to identify patterns of governance failure and missed opportunities to build resilience. Ultimately, this volume provides crucial insights into the historical baggage that the United States brings to multilateral climate negotiations, helping to explain its often frustrating role on the international stage. This book is essential reading for students, researchers, and scholars in the social sciences, humanities, and environmental studies, as well as policymakers and practitioners seeking a deeper understanding of the challenges and shortcomings of U.S. disaster mitigation policy. Chapter “‘Becoming Green:’ Resilient and Green Building as Risk Mitigation in Atlanta, Georgia” is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.